Financial covenants in syndicated lending transactions - A. A. Tarasov (Управление)
The article analyzes the use of financial covenants in international syndicated lending transactions. From a borrower’s point of view, acceptable levels of financial covenants allow to realize the transaction with comfortable conditions for further fulfillment. For lenders, an acceptable level of financial covenants is important for obtaining internal credit approval for participation in the transaction and as a tool for monitoring the credit quality of a borrower when servicing a syndicated loan. The main financial covenants of syndicated loan transactions include restrictions on the following financial ratios of a borrower: net debt/EBITDA, net interest payments/EBITDA, and net debt/equity. Lenders monitor financial covenants through a compliance certificate that a borrower sends to the lending agent on a regular basis. One of the key roles in syndicated lending transactions is played by a loan agent, through whom communications between a borrower and lenders take place. If a borrower violates the financial covenants, the process of obtaining lenders’ consent to a one-time waiver (Waiver Request) or amendment of the loan agreement (Amendment Request) is initiated. The article discusses the main stages of these processes with an indication of the participants’ roles in these processes (borrower, loan agent, lenders, and legal counsel).